Vector–Hexamer PCR Isolation of All Insert Ends from a YAC Contig of the Mouse Igh Locus - Herring, Christopher D.; Chevillard, Christophe; Johnston, Sean L.; Wettstein, Peter J.; Riblet, Roy

(untitled) (Genome Research, 1998)
We have developed a simple PCR strategy, termed vector–hexamer PCR, that is unique in its ability to easily recover every insert end from large insert clones in YAC and BAC vectors. We used this method to amplify and isolate all insert ends from a YAC contig covering the mouse Igh locus. Seventy-seven ends were amplified and sequenced from 36 YAC clones from four libraries in the pYAC4 vector. Unexpectedly, 40% of the insert ends of these YACs were LINE1 repeats. Nonrepetitive ends were suitable for use as probes on Southern blots of digested YACs to identify overlaps and construct a contig. The same strategy was used successfully to amplify insert ends from YACs in the pRML vector from the Whitehead Institute/MIT-820 mouse YAC library and from BACs in pBeloBAC11. The simplicity of this technique and its ability to isolate every end from large insert clones are of great utility in genomic investigation.[The nucleotide sequence data reported in this paper are accessible in GenBank under accession nos. B07512–B07598.]